Notes on issues on the CHOGM agenda (CARICOM Secretariat GeorgetownGY, 2003)
Highlights topics to be discussed at the Breakfast Meeting on 2 December 20003, between the Prime Minister of the United Kingdom and Heads of Government of the Caribbean Community in preparation for the Commonwealth Heads of Government Meeting in Abuja, Nigeria 5-8 December 2003.
Keywords: DEMOCRACY